2000
DOI: 10.2214/ajr.174.6.1741599
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast MR Imaging of the Fetus

Abstract: Our results indicate that ultrafast MR imaging can be used for in vivo fetal imaging, especially in assessing cerebral abnormalities. However, MR imaging should be restricted to situations in which sonographic findings are ambiguous or impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 23 publications
2
60
0
3
Order By: Relevance
“…[4] Our case highlights the great diagnostic value of MR imaging, higher than that of US, because it is able to provide a better tissue contrast and a variety of imaging planes regardless of the Letter to Editor fetal orientation. [5] It may be particularly useful in conditions as oligohydramnios or fetal head engagement where sonographic images are impaired . As in other diagnostic areas [6][7][8] , in the reported case we emphasized the role of biparametric MR imaging and underlined the usefulness of DWI.…”
mentioning
confidence: 99%
“…[4] Our case highlights the great diagnostic value of MR imaging, higher than that of US, because it is able to provide a better tissue contrast and a variety of imaging planes regardless of the Letter to Editor fetal orientation. [5] It may be particularly useful in conditions as oligohydramnios or fetal head engagement where sonographic images are impaired . As in other diagnostic areas [6][7][8] , in the reported case we emphasized the role of biparametric MR imaging and underlined the usefulness of DWI.…”
mentioning
confidence: 99%
“…Historically, USS has been the imaging choice for prenatal assessment of fetal abnormalities due to its accuracy and safety, ease of use as well as low cost and availability 13 . However, more recently, ultrafast MRI has become a practical imaging tool for prenatal diagnosis, predominantly in patients with complex fetal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Since its first use in the 1990s, fetal magnetic resonance imaging (MRI) has been adopted widely for fetal brain analysis 1,2 , with more recent uses including the depiction of abnormalities of the fetal abdomen and gastrointestinal tract 3 -6 . The MRI appearance of the normal fetal gastrointestinal tract has been depicted and depends on gestational age 4,5 .…”
Section: Use Of Fetal Magnetic Resonance Imaging In Differentiating Imentioning
confidence: 99%
“…For (patho)physiological and diagnostic reasons it would be helpful to be able to quantify human fetal swallowing movements, as has been suggested previously 1,2 . We performed a literature search via PubMed on this topic (searching until 2005) and found that no-one except Petrikovsky et al 3 has ever quantified human fetal swallowing movements.…”
Section: Quantification Of Fetal Swallowing By Ultrasound Is Impossiblementioning
confidence: 99%